TOLERANSI DALAM ISLAM DALAM KAJIAN HADIS - Nurliana Damanik (SHAHIH (Jurnal Ilmu Kewahyuan), 2019)
Tolerance in Arabic is called "tasamuh" which means to be generous, which is to be generous in association. Another word for tasamuh is "tasahul" which means hopefully. Tolerance teaches that we should have the character of being broad-minded, big-hearted, broad-minded and not imposing our own will, giving others the opportunity to think even if we differ from our opinions. All of that is in order to create harmony in religious life in society. Thus the existence of differences in understanding in a problem, such as religion and belief should not be a reason for mengadakn dividing lines in association. So tolerance requires the harmony of life among people who have various understandings and harmonization of relationships between those who are far from being rigid, especially confrontational ones.Tolerance is the attitude of making it easy, generous, quiet, and appreciative as defined by lexicograph experts both English and Arabic. Islam is a religion that makes tolerance an important part, this attitude is more applied in the area of social interaction as shown by the attitude of the Prophet. against non-Muslims in his day he was still alive. The attitude of tolerance in religion is respecting other religious beliefs by not being syncretic, namely by equating other religious beliefs with Islamic beliefs themselves, carrying out their beliefs and worship. The attitude of tolerance cannot be understood separately from the frame of the Shari'a, because if it happens, it will cause a misunderstanding of the meaning which results in the mixing between the right and the wrong. The teachings of tolerance are inherent in the principles of Islamic teachings as they are in Iman, Islam, and Ihsan.